Mean Platelet Volume and Neutrophil Lymphocyte Ratio as Related to Inflammation Markers and Anti-CCP in Rheumatoid Arthritis - Gökmen, F.; Akbal, A.; Reşorlu, H.; Binnetoğlu, E.; Cevizci, S.; Gökmen, E.; Köse, M. M.; Türkyılmaz, A. K.; Akbal, E. (Aktuelle Rheumatologie, 2016)
Background: Various thrombocyte markers and white blood cell levels and their subtypes have recently been investigated in association with inflammation. The purpose of this study was to determine the correlation of mean platelet volume (MPV) and neutrophil/lymphocyte ratio (NLR) with disease activation and clinical parameters in rheumatoid arthritis (RA) patients.Methods: 84 RA patients and 60 healthy controls were included. Platelet, MPV, white cell, neutrophil and lymphocyte levels in full blood counts were investigated, and NLR was calculated. Erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), rheumatoid factor (RF), anti-cyclic citrullinated peptide (anti-CCP), disease activation score (DAS 28) and a health assessment questionnaire (HAQ) were used in the evaluation of RA.Results: In the present study a total of 144 patients was enrolled, 84 with RA and 60 healthy individuals. 75.2% (n=108) were women and 24.8% (n=36) were men. The patients with RA had lower MPV than control individuals (MPV; 8.52±1.15 fL and 8.92±0.87 fL, respectively) and CRP (r:−0.234, p=0.005). RA patients’ mean NLR was significantly higher than that of the control group (2.74±1.74 and 1.80±0.78, respectively; p<0.001). Furthermore, anti-CCP positive patients had higher NLR than anti-CCP negative patients (NLR; 2.51±1.92 and 1.95±1.22, p=0.019 respectively). NLR was positively correlated with ESR (r=0.190, p=0.023), CRP (r=0.230, p=0.035) and anti-CCP (r=0.300, p=0.005).Conclusion: In conclusion, MPV and NLR together with acute phase reactants can be a useful index for showing inflammation in RA patients.
Keywords: rheumatoid arthritis; mean platelet volume; neutrophil-to-lymphocyte ratio; inflammation